2015
DOI: 10.1038/srep13499
|View full text |Cite
|
Sign up to set email alerts
|

Very low embryonic crude oil exposures cause lasting cardiac defects in salmon and herring

Abstract: The 1989 Exxon Valdez disaster exposed embryos of pink salmon and Pacific herring to crude oil in shoreline spawning habitats throughout Prince William Sound, Alaska. The herring fishery collapsed four years later. The role of the spill, if any, in this decline remains one of the most controversial unanswered questions in modern natural resource injury assessment. Crude oil disrupts excitationcontraction coupling in fish heart muscle cells, and we show here that salmon and herring exposed as embryos to trace l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 56 publications
(82 reference statements)
3
117
1
3
Order By: Relevance
“…Chinook salmon supported the inclusion of the EVOS covariate in explaining variation in productivity relative to the models that only included density dependence (Table 1), but the estimated impact of EVOS was slightly positive and opposite of what we might expect from other studies [16]. Coefficients for these impacts and all hypotheses are included online, https://github.com/NCEAS/pfx-covariation-pws.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Chinook salmon supported the inclusion of the EVOS covariate in explaining variation in productivity relative to the models that only included density dependence (Table 1), but the estimated impact of EVOS was slightly positive and opposite of what we might expect from other studies [16]. Coefficients for these impacts and all hypotheses are included online, https://github.com/NCEAS/pfx-covariation-pws.…”
Section: Resultsmentioning
confidence: 72%
“…Incardona et al [16] suggested a mechanism by which detrimental effects could result from low toxicity 7–9 months after exposure, fine scale sampling of individual exposure rates immediately following a spill could be combined with intensive spatiotemporal histology sampling in the years that follow.…”
Section: Resultsmentioning
confidence: 99%
“…The identification of alkylated PAHs in crude oil‐exposed marine organisms is critical for evaluation of the toxicity observed in these species. Several studies report alkyl homologue cluster concentration in different fish tissue matrices using GC/MS SIM methods . However, relatively large quantities (several grams) of sample material are needed to obtain the necessary sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…In the United States, herring eggs and larvae have been a focus of both field and laboratory studies to assess the ecological impacts of large oil spills, including the 1989 Exxon Valdez spill in Alaska (Carls et al, 1999;Marty et al, 1997) and the 2007 Cosco Busan spill in San Francisco Bay (Incardona et al, 2012a;Incardona et al, 2012b). They have also provided a context for mechanistic studies on crude oil cardiotoxicity (Incardona, et al, 2009;Incardona, et al, 2015). As indicated in Fig.…”
Section: Accumulation Of Edema In Demersal Marine Speciesmentioning
confidence: 98%
“…2). These effects range from outright embryonic heart failure and mortality at relative high PAH exposures (Adams et al, 2014a;Adams et al, 2014b;Esbaugh et al, 2016;Incardona et al, 2014;Incardona et al, 2013;Jung et al, 2013;Jung et al, 2015;Madison et al, 2015;Martin et al, 2014;McIntyre et al, 2016a;McIntyre et al, 2016b;Sørhus et al, 2015), to more subtle effects on heart shape and delayed impacts on cardiovascular performance at lower concentrations (Hicken et al, 2011;Incardona et al, 2015). These latter, protracted physiological impacts likely contributed to the delayed mortality and poor population recruitment previously observed both in 1) mark-recapture studies with pink salmon (Oncorhynchus gorbuscha) exposed to crude oil during embryogenesis (Heintz, 2007;Heintz et al, 2000) and 2) the losses of wild pink salmon spawned in shoreline habitats that were oiled in the aftermath of the 1989 Exxon Valdez disaster (Rice et al, 2001).…”
Section: Introductionmentioning
confidence: 99%